2013
DOI: 10.1017/jfm.2013.599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluid inertia on the dynamics and scaling of neutrally buoyant particles in shear flow

Abstract: The basic dynamics of a prolate spheroidal particle suspended in shear flow is studied using lattice Boltzmann simulations. The spheroid motion is determined by the particle Reynolds number (${\mathit{Re}}_{p} $) and Stokes number ($\mathit{St}$), estimating the effects of fluid and particle inertia, respectively, compared with viscous forces on the particle. The particle Reynolds number is defined by ${\mathit{Re}}_{p} = 4G{a}^{2} / \nu $, where $G$ is the shear rate, $a$ is the length of the spheroid major s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 28 publications
7
80
0
Order By: Relevance
“…This explains why stable log-rolling is not observed in DNS [3][4][5][6] at the smallest shear Reynolds numbers accessible in the simulations. Moreover, we find that tumbling in the flow-shear plane is stable for prolate particles.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…This explains why stable log-rolling is not observed in DNS [3][4][5][6] at the smallest shear Reynolds numbers accessible in the simulations. Moreover, we find that tumbling in the flow-shear plane is stable for prolate particles.…”
Section: Introductionmentioning
confidence: 88%
“…The question is currently of great interest: several recent papers have reported results of direct numerical simulations (DNSs) of the problem, using "lattice Boltzmann" methods. [3][4][5][6] These studies reveal that fluid and particle inertias affect the orientational dynamics of a neutrally buoyant spheroid in a simple shear in intricate ways. The DNSs are performed at moderate and large shear Reynolds numbers, defined as Re s = sa 2 /ν, where a is the largest particle dimension, s is the shear strength, and ν the kinematic viscosity of the suspending fluid.…”
Section: Introductionmentioning
confidence: 93%
“…Leal (1980) provides a review of the older literature, and a wide range of work has followed, for example: Koch & Shaqfeh (1989); Szeri & Leal (1993); Herzhaft et al (1996); Olson & Kerekes (1998); Parsa et al (2011); Rosen et al (2014); Andersson & Soldati (2013). Turbulent flows advecting anisotropic particles provide a compelling test case, both because of the many applications and because of the nearly universal statistics of the velocity gradients experienced by small particles in many turbulent flows at large Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of inertia on path selection of a capsule at a bifurcation remains unknown. In other systems, for example non-spherical particles in shear flows, it has been shown that inertial effect could fundamentally change the dynamics of particles even at low Reynolds number (Rosén, Lundell & Aidun 2014;Dabade, Marath & Subramanian 2016). Furthermore, when a capsule approaches the bifurcation, it can sustain high shear stresses, which may damage the capsule membrane.…”
mentioning
confidence: 99%